The Role of Founder and Other Family Participation on US Private Foundation Efficiency. (February 2017) - McAllister, Brian; Allen, Arthur
Abstract: Founders make significant financial contributions in creating US private foundations. Therefore, we hypothesize that founders monitor foundation operations and predict a positive relation between founder participation and foundation efficiency. In contrast, we propose competing hypotheses in examining the relation between other family member participation and foundation efficiency. Other family member participation has the potential to enhance foundation efficiency if founders are able to transfer their philanthropic values to their progeny. However, other family participation also has the potential to diminish foundation efficiency if the founders' withdrawal leaves their foundations without true principals to monitor managerial actions. We find that both founder and other family participation are positively associated with foundation efficiency. We also provide limited evidence that the positive association between founding family participation and foundation efficiency is transferred to second generation family members, but is not transferred to subsequent generations.